ASSESSMENT OF BUSINESS ACTIVITY OF LLC «ELAN-95» - S. Bychkova (Publishing House of the State University of Management, 2017)
Assessment of business activity of LLC «Elan-95» for 2007-2015 is carried out. Efficiency of usage of current assets of the organization is analyzed. The analysis of indicators of business and market activity of LLC «Elan-95» is carried out. By results of the analysis conclusions and practical recommendations about improvement of efficiency of usage of means of the organization are carried out.